The proportional intermingling of two different exponential distribution terms
In this paper we introduce a new distribution, called proportional exponential difference (PED) distribution, such that its probability density function is in the form: <img title="f_x( x , α ,λ )=λ 1-2α ( ( 1-α )e ^-λ x1-α - α e ^-λ xα ),x≥ 0," src="https://latex.codecogs.com/gif.latex?f_x&space;(&space;x&space;,&space;α&space;,λ&space;&space;)=λ&space;1-2α&space;&space;(&space;&space;(&space;1-α&space;&space;)e&space;^-λ&space;x1-α&space; &space;-&space;α&space;e&space;^-λ&space;xα&space; &space;&space;),x≥&space;0,"> where 0" src="https://latex.codecogs.com/gif.latex?λ&space;>&space;0"> และ . We study some properties of PED distribution such as expected value, variance, moment generating function and its limit at and 1. , number=1, journal=Progress in Applied Science and Technology, author=Panomram, Waratchaya and Boonthiem, Somchit and Khotama, Supawan and Klongdee, Watcharin, year=2016, month=Jun., pages=164–169